2001
DOI: 10.1530/eje.0.1450529
|View full text |Cite
|
Sign up to set email alerts
|

Maternal glucocorticoid treatment modulates placental leptin and leptin receptor expression and materno-fetal leptin physiology during late pregnancy, and elicits hypertension associated with hyperleptinaemia in the early-growth-retarded adult offspring

Abstract: Background: Leptin concentrations are increased during late pregnancy, and leptin receptors are expressed in placental and fetal tissues, suggesting a role for leptin in placental and/or fetal growth, or both. In humans, leptin concentrations in adulthood are inversely related to body weight at birth, independent of adult adiposity, and correlate with fasting insulin. Glucocorticoids and insulin regulate leptin secretion. Excessive exposure to glucocorticoids during late fetal development in the rat causes int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 71 publications
10
88
3
1
Order By: Relevance
“…During pregnancy, glucocorticoids belong to factors that reduce insulin sensitivity in the dam, activate adipogenesis by differentiation of pre-adipocytes (Breton, 2013) and promote, in sheep, the synthesis and secretion of leptin in the fetus (Forhead and Fowden, 2009). It has been suggested that the glucocorticoid surge that is characteristic of late gestation may also downregulate placental leptin production (Sugden et al, 2001). Changes in either fetal or maternal leptin levels may be important for parturition or late fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, glucocorticoids belong to factors that reduce insulin sensitivity in the dam, activate adipogenesis by differentiation of pre-adipocytes (Breton, 2013) and promote, in sheep, the synthesis and secretion of leptin in the fetus (Forhead and Fowden, 2009). It has been suggested that the glucocorticoid surge that is characteristic of late gestation may also downregulate placental leptin production (Sugden et al, 2001). Changes in either fetal or maternal leptin levels may be important for parturition or late fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Other regulatory parallels include the effects of glucocorticoids, which in addition to up-regulating the putative FPF in the lung (Bolt et al 2001), increase leptin synthesis and release by human adipocytes (Leal-Cerro et al 2001), and enhance leptin levels in preterm infants (Ng et al 2002). Moreover, the co-culture of human placental trophoblast cells with glucocorticoids has been observed to enhance leptin release (Coya et al 2001), while maternal glucocorticoid treatment resulted in an up-regulation of placental leptin receptor protein in rat pregnancy (Sugden et al 2001). Therefore, with respect to: (i) the effects of androgens and glucocorticoids; (ii) the common tissues of origin of both leptin and the putative regulator; and (iii) the similarities in the molecular masses of leptin and the proposed FPF (Bergen et al 2002, Torday & Rehan 2002, leptin has been suggested by as a logical FPF candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, stress-induced high levels of maternal glucocorticoids can cross the placenta (Takahashi et al, 1998). DEX readily crosses the placenta and is not inactivated by 11bHSD2, suggesting that bypassing this system may contribute to low birth weight and fetal programming of hypertension (Benediktsson et al, 1993;Nyirenda et al, 1998;Sugden et al, 2001). In further support of this idea, inhibition of 11bHSD2 by carbenoxolone during gestation produces hypertension in adult offspring (Langley-Evans, 1997).…”
Section: Role Of the Placentamentioning
confidence: 94%
“…Other outcomes associated with these maternal treatments are altered insulin sensitivity (Ozanne et al, 1996;Sugden and Holness, 2002;Fernandez-Twinn et al, 2005), increased fat deposition (Bellinger et al, 2006), and impaired renal function (Woods et al, 2004). It is unclear whether fetal programming stems primarily from nutritional status or through endocrine alterations in the mother and fetus (or both) because prenatal glucocorticoid exposure produces metabolic effects similar to those seen in IUGR models (Benediktsson et al, 1993;Nyirenda et al, 1998;Sugden et al, 2001;Tamashiro et al, 2009). …”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation